Development of Burnout Syndrome in Non-university Teachers: Influence of Demand and Resource Variables - Llorca-Pellicer, Marta; Soto-Rubio, Ana; Gil-Monte, Pedro R. (Frontiers in Psychology, 2021)
Psychosocial risks at work are an important occupational problem since they can have an impact on workers' health, productivity, absenteeism and company profits. Among their consequences, the burnout stands out for its prevalence and associated consequences. This problem is particularly noteworthy in the case of teachers. The aim of the study was analysed the influence of some psychosocial factors (demand and resource variables) and risks, specially the emotional labor, in the burnout development taking into consideration the levels of burnout according to the Spanish Burnout Inventory (SBI). This paper contributes to advancing knowledge on this issue by analysing the influence of work characteristics (including emotional aspects of work) and personal characteristics on the progress of burnout. The sample were 8235 non-university teachers (2268 men 27.5% and 5967 women 72.5%), aged 22 to 70 (M=45.16, SD= 9.18). To this purpose, statistical modelling by logistic regression was used. The results on this study showed that No burnout level was positively related with resources variables and negatively with demand variables. In the Medium-High levels and the higher levels of burnout levels (i.e., Profile 1 and Profile 2), there are a positive relation with demand variables and negative with resources variables. In conclusion, demand variables cause an increase in the burnout levels, influencing positively in the movements between the levels of No burnout to Medium-High levels of burnout and Medium-High levels to Profile 1. While, resources variables had a negative influence on it. However, the results in the movement between Profile 1 and Profile 2 weren’t expected, the variables Social support and Resources at work, had a positive relation with on the movement between Profile 1 to Profile 2. Therefore, these variables could contribute to increase feelings of guilt and risk of higher burnout.